EXPANDING MEDIA COMPETENCE THROUGH COMPUTER SCIENCE AND INFORMATION TECHNOLOGY EDUCATION: AN INTERDISCIPLINARY IMPERATIVE - Fayzieva, Dildora (Journal of Higher Education and Academic Advancement, 2025)
Objective: This study investigates the integration of computer science and information technology (IT) education to enhance students’ media competence, a critical skill in an era marked by rapid digitalization and widespread misinformation. Method: Employing a mixed-methods approach, the research combines quantitative analysis of student performance with qualitative data from classroom observations and interviews. The study engaged both secondary and university-level students through a tailored curriculum incorporating coding, data analysis, and media evaluation tasks, supported by digital tools such as educational platforms, coding simulations, and media annotation software. Results: The findings reveal a marked improvement in students’ critical assessment of digital content, source verification, and bias recognition. Students also demonstrated increased confidence in navigating digital environments and applying computational thinking to media challenges, with collaborative learning and engagement notably enhanced among diverse learners. Novelty: This study presents a novel interdisciplinary framework that merges technical and critical thinking skills, underscoring the potential of cross-curricular strategies to foster media literacy and prepare students as informed digital citizens.